2023
DOI: 10.1109/access.2023.3243252
|View full text |Cite
|
Sign up to set email alerts
|

Solar Radiation Forecasting Based on the Hybrid CNN-CatBoost Model

Abstract: The renewable energy industry is rapidly expanding due to environmental pollution from fossil fuels and continued price hikes. In particular, the solar energy sector accounts for about 48.7% of renewable energy, at the highest production ratio. Therefore, climate prediction is essential because solar power is affected by weather and climate change. However, solar radiation, which is most closely related to solar power, is not currently predicted by the Korea Meteorological Administration; therefore, solar radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Second, compared with the single crop coefficient model, the machine learning model can use the entire data set for training, minimize information loss, and still provide high prediction accuracy in the case of missing variables. Kim et al [32] proposed a CNN-CatBoost hybrid model solar radiation prediction method and concluded that the prediction accuracy and stability of this hybrid model is better than the single model of CNN and CatBoost; Niu et al [33] introduced a machine learning method based on wavelet packet denoising and CatBoost for weather forecasting. Using a feature selection and spatio-temporal feature addition to improve forecasting performance, the results show that the CatBoost model combined with wavelet packet denoising can achieve shorter convergence time and higher forecasting accuracy than forecasting models using deep learning or machine learning algorithms alone.…”
Section: Discussionmentioning
confidence: 99%
“…Second, compared with the single crop coefficient model, the machine learning model can use the entire data set for training, minimize information loss, and still provide high prediction accuracy in the case of missing variables. Kim et al [32] proposed a CNN-CatBoost hybrid model solar radiation prediction method and concluded that the prediction accuracy and stability of this hybrid model is better than the single model of CNN and CatBoost; Niu et al [33] introduced a machine learning method based on wavelet packet denoising and CatBoost for weather forecasting. Using a feature selection and spatio-temporal feature addition to improve forecasting performance, the results show that the CatBoost model combined with wavelet packet denoising can achieve shorter convergence time and higher forecasting accuracy than forecasting models using deep learning or machine learning algorithms alone.…”
Section: Discussionmentioning
confidence: 99%
“…Although their combined approach enhanced forecasting performance, the complexity of integrating various forecasting models may pose challenges for implementation and interpretation operations. Kim et al [12] applied a Hybrid CNN-CatBoost Model for solar radiation forecasting, achieving high accuracy. However, the validation of this model is limited to specific weather conditions, potentially constraining its generalizability to diverse environmental settings.…”
Section: In-depth Review Existing Modelsmentioning
confidence: 99%
“…Compared to the popular bagging (i.e., Random Forest) and other boosting (i.e., Extreme Gradient Boost, Light Gradient Boosting Machine) methods, CB returns reliable performance with fewer hyperparameters, which is claimed as the advantage of the ordered boosting tree approach and the L2 parameter regularization parameter (Prokhorenkova et al, 2018). The novel decision tree approaches introduced in CB help reduce overestimation, and improve prediction accuracy for any given dataset (Fan et al, 2018;Kim et al, 2023). In this study, we validate the performance of CB machine learning in (1) evaluating the relationship between environmental and ecological factors and the distribution of Indo-Pacific eels (A. marmorata) in central Vietnam and (2) comparison with a multivariate linear model to estimate the growth of Indo-Pacific eel (A. marmorata) in length across different stages of development.…”
Section: Introductionmentioning
confidence: 99%